Potential of PGPR from Rhizospheric Grass in Bromo Tengger Semeru National Park, Indonesia, against Xanthomonas oryzae pv. oryzae - Femita Hapsari; Ahmad Muhidin; Luqman Qurata Aini; Rina Rachmawati (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2025)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most destructive diseases affecting rice, resulting in significant yield losses and reduced grain quality. The overuse of chemical bactericides has raised environmental concerns and contributed to the emergence of resistant pathogen strains, emphasizing the need for sustainable alternatives. Plant Growth-Promoting Rhizobacteria (PGPR) offer a promising alternative due to their dual role in enhancing plant growth and suppressing phytopathogens. This study aimed to isolate and characterize PGPR from the rhizosphere of Imperata cylindrica, a grass species thriving in the extreme sand sea environment of Bromo Tengger Semeru National Park (BTSNP), Indonesia. The sampling site represents a unique volcanic soil ecosystem characterized by sandy texture, high surface temperatures, and nutrient-poor conditions, with no vegetation other than I. cylindrica. These extreme environmental conditions suggest that the associated microbial communities may be highly adapted to abiotic stress and possess valuable traits for plant growth promotion and pathogen suppression. A total of 46 rhizobacterial isolates were obtained, of which five (Isolates 5, 6, 8, 10, and 12) demonstrated nitrogen-fixing ability, phosphate-solubilizing activity, and strong antagonism against Xoo. Morphological, physiological, and biochemical analyses identified Isolates 5, 8, and 12 as Pantoea spp., while Isolates 6 and 10 were classified as Erwinia spp. In vitro inhibition assays revealed that Isolate 6 exhibited the highest antagonistic activity, comparable to streptomycin, and was categorized as